Key aspects for the genetic transformation of rice (Oryza sativa L.) subspecies indica by Agrobacterium tumefaciens - Aguilar-Bartels, Cindy Marié (2021)
Introduction. Agrobacterium-mediated transformation of rice (Oryza sativa L. ssp indica) represents an opportunity for scientific research and genetic improvement. Optimization of the protocol is necessary to obtain the highest transformation efficiency. Objective. To evaluate different factors that affect the genetic transformation in embryogenic rice callus of subspecies indica through Agrobacterium tumefaciens. Materials and methods. This study was performed in San José, Costa Rica between 2012 and 2014. The following were evaluated in six treatments: the effect of callus age, acetosyringone concentration, lighting condition, the presence or absence of radicle, and Agrobacterium tumefaciens strain on the genetic transformation of embryogenic calli of rice variety CR5272 with gus reporter gene. Agrobacterium strains LBA4404 with pCAMBIA1305.2 plasmid, and strains ATHV, GV3101, and LBA4404 with the pCAMBIA 1303 plasmid were compared; by histochemical tests for the detection of transient expression of the β-glucuronidase reporter gene. Results. The evaluation of the six treatments with strain LBA4404::pCAMBIA 1305.2 resulted in transient expression of 1.33-7.00 % of the GusPlus gene for the CR5272 variety, and 8.00 % for the control with the Nipponbare (ssp. japonica) variety. The strains with the pCAMBIA1303 plasmid showed a transient expression of the gusA gene between 100-65 % with an average area of 14.23 mm2 (ATHV), 8.81 mm2 (GV3101), and 8.83 mm2 (LBA4404) with no significant differences between them; however, there were differences when compared with strain LBA4404::pCAMBIA1305.2 (85 %, 4.39 mm2). Conclusions. The use of the conditions: six-day callus, acetosyringone concentration of 76 µM, light before and after cocultivation, presence of radicle and the ATHV::pCAMBIA 1303 , improved the transformation efficiency with Agrobacterium tumefaciens in the rice variety CR5272.